PHOENIX DACTYLIFERA FRUIT EXTRACT AMELIORATES ALTERED BIOCHEMICAL PARAMETERS IN STREPTOZOTOCIN-INDUCED DIABETES MELLITUS ALBINO RATS - A. O., OGO; S. F., ABAH; B., INALEGWU; U. E., ERU (International Journal of Current Pharmaceutical Research, 2020)
Objective: Consistent projections have indicated a steady increase in the global burden of diabetes mellitus. Given the increased cost in conventional management of the condition in addition to reported side effects and cost of orthodox management, attention is shifting to the use of alternative methods such as plants materials with dual benefits as food and medicine. Thus, this study was designed to investigate the effect of date palm fruit on some biochemical parameters in streptozotocin-induced wistar rats. Methods: Animals were divided into 5 groups of 6 rats each (I as normal control, II as diabetic control and 3-5 as extract-treated groups) maintained for 14 d. At the end of the treatment, the animals were fasted overnight, then sacrificed and blood samples collected for analysis of biochemical parameters (including blood glucose, blood lipids and enzymes). Results: The results show that treatment of diabetic animals with extract of date palm fruit show a significant (P<0.05) reduction in glucose levels in groups II–V compared to group I. Similar positive effects were observed in the levels of lipids and enzymes in treated groups compared to diabetic control group II. A GC-MS analysis of the fraction of the fruit extract revealed some bioactive compounds that may be responsible for the effects exhibited in the study. Conclusion: These findings which demonstrate the ameliorative effect on hyperglycemia and hyperlipidemia, further support the use of date palm fruit as a nutraceutical agent.